Pyrrolizidine alkaloids and other constituents from Emilia fosbergii Nicolson. (October 2020) - Freitas, Jolindo A.; Ccana-Ccapatinta, Gari V.; Da Costa, Fernando B.
Abstract: Emilia fosbergii is a member of the tribe Senecioneae (Asteraceae), most species of which contain pyrrolizidine alkaloids. Notwithstanding, the phytochemistry of E. fosbergii is poorly understood, and pyrrolizidine alkaloids produced by this species have yet to be characterized. In this work, the presence of 11 pyrrolizidine alkaloids, three caffeoylquinic acid derivatives, and six flavonoids were detected by liquid chromatography coupled to high-resolution mass spectrometry analyses. Pyrrolizidine alkaloids of otonecine, retronecine, and platynecine bases are annotated in different parts of the plant. Furthermore, emiline was isolated, possibly indicating that E. fosbergii has a close phylogenetic relationship with E. coccinea . The chemophenetic implications of the presence of pyrrolizidine alkaloids in E. fosbergii and tribe Senecioneae are discussed. Highlights: Fifteen pyrrolizidine alkaloids were described for the first time in E. fosbergii . Six flavonoids and three chlorogenic acid derivatives were also identified. Chemophenetic significance of pyrrolizidine alkaloids in Emilia is discussed.